PROBLEMS OF UZBEK SPEECH ETIQUETTE AND SPEECH PURITY - Quldashev Nizomiddin Ahmadalievich; Jo‘oraboeva Gulruh Solijonovna; O‘rinboeva Ezozkhan Kamolovna (Western European Studies, 2024)
As we all know, nowadays the attention to language is increasing. As in any field, colloquial speech has its own standards and etiquette. This article focuses on the problems of maintaining speech etiquette and purity of speech in social groups and public places.
Keywords: etiquette; rules of etiquette; moral culture